2018
DOI: 10.1186/s12913-018-3426-x
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of Ugandan public sector health facilities to prevent and control non-communicable diseases: an assessment based upon WHO-PEN standards

Abstract: BackgroundNon-communicable diseases (NCDs) are increasing in prevalence in low-income countries including Uganda. The Uganda Ministry of Health has prioritized NCD prevention, early diagnosis, and management. However, research on the capacity of public sector health facilities to address NCDs is limited.MethodsWe developed a survey guided by the literature and the standards of the World Health Organization Pacakage of Essential Noncommunicable Disease Interventions for Primary Health Care in Low-Resource Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 19 publications
11
78
0
Order By: Relevance
“…The dissimilarities may be explained by the differences in stroke care and management as well as type of rehabilitation programs between countries. However in Uganda, the presence of continuum of poverty [26] may lead to poor accessibility to hospital care, late presentation of severe stroke and poor compliance to medication with eventual poor health outcomes [8]. A recent study in Uganda found that only 27% of medicines and 32% of diagnostic tests for diabetes and cardiovascular disease were affordable by most people [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dissimilarities may be explained by the differences in stroke care and management as well as type of rehabilitation programs between countries. However in Uganda, the presence of continuum of poverty [26] may lead to poor accessibility to hospital care, late presentation of severe stroke and poor compliance to medication with eventual poor health outcomes [8]. A recent study in Uganda found that only 27% of medicines and 32% of diagnostic tests for diabetes and cardiovascular disease were affordable by most people [27].…”
Section: Discussionmentioning
confidence: 99%
“…All-stroke mortality from the available Ugandan hospital-based studies, is estimated to be between 30 and 40% at 1 month [5,6], which is much higher than the 20% mortality reported in the rest of the world [7]. Hence, the increasing burden of stroke in the SSA region will put a huge burden on the already overstretched health care system and resources [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was an observed heterogeneity of the study ndings. Among the 19 studies conducted in one region of SSA, the majority were from the Eastern region (n = 11, 58%) [11][12][13][14][15][16][17][18][19][20][21]. About 26% (n = 5) [22][23][24][25][26]and 16% (n = 3) [27][28][29] of the remaining studies were conducted in the Southern and Western region respectively.…”
Section: Study Characteristics Methodological Quality and Risk Of Biasmentioning
confidence: 99%
“…A total of 14 studies (66.7%) investigated the availability of at least one diagnostic test for DM. Among the recommended diagnostic tests for DM in the WHO PEN, availability of blood glucose tests was the most investigated (13 studies, 92.9%) [11, 13, 14, 17-22, 26-29, 31] while microalbuminuria tests were the least investigated (2 studies, 14.3%) [11,20].…”
Section: Statinsmentioning
confidence: 99%